Benchmarking Framework For Reading And Knowledge Growth : A Malaysian Case - Parveen, Kaur; Arif, Jawaid; Davis, Johnraj; Sivashunmugam, Sangaran; Than Myint, Khin; M. Ikram, Ul Haq; Humaira, Ramzan (Webology Center, 2022)
Benchmarking though a daily activity that remains unnoticeable by many of us and researchers seem unaware of this quality approach. This paper highlights significance of benchmarking in knowledge growth discipline. The authors try to emphasise knowledge growth because it seems neglected due to variety of reasons. In this regard, benchmarking research method started with fieldwork (visits to the benchmarked libraries), informal interviews and literature review. This helped in formulation of workable Best Practices framework. A constant comparative analysis process (benchmarking) was carried out focusing mainly on data collection, coding and analysis. Consequently, this iterative process led to the development of a framework to find the extent of knowledge growth against workable Best Practices. This framework is prelude to a comprehensive one in future for the use of variety of stakeholders including heads of library institutions, librarians, NGOs involved in knowledge growth, teachers and library users.